Reflection of Cultural Identity in the Latest Diary Fragments of Alfonsas Nyka-Niliūnas (2009–2012) and Essay Book “Levels of Life” by Julian Barnes - Mykolaitytė, Aurelija (Respectus Philologicus, 2019)
The article compares the following two texts: the latest dairy fragments of Alfonsas Nyka-Niliūnas (2014) and the essay book “Levels of Life” by Julian Barnes. Both writers aim to reveal personal experiences through cultural texts: the relationship with the Other enables us to identify ourselves and helps to describe our inner world. The article focuses on how the memory is created and what is the most important in culture for both writers. Several meaningful aspects are emphasized by both writers: they both raise existential questions, search for possible answers in culture, as well as search for links with a particular place and focus on art. The study has revealed that that culture, especially classic European culture, is an essential support that allows us to reflect our being. Special attention is paid to French culture, which could be perceived as a benchmark for the European mentality. Although the books refer to different cultural sources, they both focus on a great respect of the art of the word as capable of preserving memory.